1996
DOI: 10.1007/bf02523383
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐catalyzed production of biodiesel

Abstract: ABSTRACT:Lipases were screened for their ability to transesterify triglycerides with short-chain alcohols to alkyl esters. The lipase from Mucor miehei was most efficient for converting triglycerides to their alkyl esters with primary alcohols, whereas the lipase from Candida antarctica was most efficient for transesterffying triglycerides with secondary alcohols to give branched a|kyl esters. Conditions were established for converting tallow to short-chain alkyl esters at more than 90% conversion. These same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
233
0
15

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(257 citation statements)
references
References 21 publications
9
233
0
15
Order By: Relevance
“…Reference with reported use for biodiesel Hsu et al (2001), Nelson et al (1996) Beef and mutton tallow Stevenson et al (1994) Cotton oil soapstock Keskin et al (2008) …”
Section: Appendixmentioning
confidence: 99%
“…Reference with reported use for biodiesel Hsu et al (2001), Nelson et al (1996) Beef and mutton tallow Stevenson et al (1994) Cotton oil soapstock Keskin et al (2008) …”
Section: Appendixmentioning
confidence: 99%
“…This is because alkali process is more efficient and less corrosive than the acid process. As for the enzyme-catalyzed system, it requires a much longer reaction time than the other two catalysts (Nelson et al, 1996;Watanabe et al, 2001). Alkali-catalyzed transesterification studies have been reported (Freedman et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…동, 식물성 오일과 알코올을 촉매 하에서 반응하면 지방산메 틸에스테르와 글리세롤이 생성되며 지방산메틸에스테르상을 정제하면 바이오디젤이 얻어진다 [8][9][10]. 부산물로 생성된 글리 세롤은 제약, 식품 및 플라스틱 제품에 순도에 맞게 정제되어 이용되고 있다 [7].…”
Section: 서 론unclassified